2004
DOI: 10.1186/1475-2875-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Timely and accurate information about the onset of malaria epidemics is essential for effective control activities in epidemic-prone regions. Early warning methods that provide earlier alerts (usually by the use of weather variables) may permit control measures to interrupt transmission earlier in the epidemic, perhaps at the expense of some level of accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Despite the significance of weather variables in seasonal patterns of malaria, this analysis was not able to provide any evidence of a link between weather anomalies and unusually high incidence of malaria (e g, unseasonably high rainfall leading to a peak in malaria incidence), which is in line with previous findings [12,31]. This may indicate that unusually high incidence of malaria is not driven by unusual weather patterns in the counties, and rather, is mediated by other factors such as human behaviour, movement patterns, migration, or agricultural practices.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the significance of weather variables in seasonal patterns of malaria, this analysis was not able to provide any evidence of a link between weather anomalies and unusually high incidence of malaria (e g, unseasonably high rainfall leading to a peak in malaria incidence), which is in line with previous findings [12,31]. This may indicate that unusually high incidence of malaria is not driven by unusual weather patterns in the counties, and rather, is mediated by other factors such as human behaviour, movement patterns, migration, or agricultural practices.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, higher maximum temperature seemed to have a negative effect on mosquito density. Maximum temperature could also influence mosquito survival and may result in breeding sites drying up faster after seasonal rains in cold environments such as the current study area [37]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the major driving force of malaria transmission is climate [4-8]. However, the data has been largely inconsistent as to exactly how climate influences malaria transmission.…”
Section: Introductionmentioning
confidence: 99%